A Literature Review on the Sustainable EPQ Model, Focusing on Carbon Emissions and Product Recycling - Rubayet Karim; Koichi Nakade (Logistics)
Background: Many businesses want to include sustainability in their manufacturing operations. A conventional economic production quantity (EPQ) model is employed to calculate the ideal number of products to manufacture at one time. The goal of this study was to look at the current research on sustainable economic production quantity and supply chain models and suggest prospective future research directions based on existing knowledge gaps. Methods: In this perspective, we used systematic procedures to conduct a survey that included studies from two scenarios: (1a) a sustainable EPQ model that accounts for carbon emissions from inventory storage and manufacture, (1b) a sustainable EPQ model that includes product recycling, and (2) a reverse logistics model that accounts for emissions and product recycling. Results: According to the inquiry, there are reverse logistics models in the literature that consider carbon emissions and product recycling together, but they are not jointly considered for modeling a sustainable EPQ model considering the situation where the manufacturing system is imperfect, although both are vital for ensuring environmental sustainability. Conclusions: In the future, the EPQ model can be developed with these two aspects in mind to understand the effects of product recycling on carbon emissions while controlling production and inventories for an imperfect manufacturing system.